2011
DOI: 10.1029/2011jd016526
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-Southern Oscillation sensitivity to cumulus entrainment in a coupled general circulation model

Abstract: [1] A series of 200 year long integrations is performed using the Geophysical Fluid Dynamics Laboratory CM2.1 by varying the Tokioka parameter, a minimum entrainment rate threshold in the cumulus parameterization. Changing the threshold alters both the tropical Pacific mean state and the El Niño-Southern Oscillation (ENSO) variability. Increasing the Tokioka parameter causes a basin-wide cooling in the tropical Pacific with the reduction of high clouds. The degree of cooling in the western part of the basin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 33 publications
3
51
1
Order By: Relevance
“…This may be because the model does not properly represent ocean eddy fluxes due to tropical instability waves (Jochum and Murtugudde 2006). The biases in the damping time (g 21 ) probably result from inadequacies in the parameterization of convection and clouds in the CM2.1 (Wittenberg et al 2006;Kim et al 2007Kim et al , 2011. For instance, Wittenberg et al (2006) showed that the convective response in the CM2.1 is shifted too far to the west, which may explain the westward shift in the CM2.1 damping time peaks as compared to the ECDA.…”
Section: A Model Results and Comparison With Ecdamentioning
confidence: 97%
“…This may be because the model does not properly represent ocean eddy fluxes due to tropical instability waves (Jochum and Murtugudde 2006). The biases in the damping time (g 21 ) probably result from inadequacies in the parameterization of convection and clouds in the CM2.1 (Wittenberg et al 2006;Kim et al 2007Kim et al , 2011. For instance, Wittenberg et al (2006) showed that the convective response in the CM2.1 is shifted too far to the west, which may explain the westward shift in the CM2.1 damping time peaks as compared to the ECDA.…”
Section: A Model Results and Comparison With Ecdamentioning
confidence: 97%
“…The Pacific climatological mean climate, particularly SSTs, has been known to influence the ENSO amplitude (An and Wang 2000;Yeh and Kirtman 2005;Kim et al 2011;Xiang et al 2013;Chung and Li 2013). Recently, Chung and Li demonstrated that the modulation of the ENSO amplitude is associated with decadal changes in the mean SST over the tropical Pacific, particularly through changes in the east-west gradient of the tropical Pacific SSTs and the precipitation changes associated with it.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Chung and Li demonstrated that the modulation of the ENSO amplitude is associated with decadal changes in the mean SST over the tropical Pacific, particularly through changes in the east-west gradient of the tropical Pacific SSTs and the precipitation changes associated with it. By using coupled model experiments with different parameter values for the convection scheme, Kim et al (2011) showed that the ENSO amplitude is sensitive to the mean precipitation over the eastern Pacific: increased mean precipitation over the eastern Pacific results in an increase in the ENSO amplitude. In their study, the increased mean precipitation over the eastern Pacific induced an eastward shift of the ENSO atmospheric component, particularly the zonal wind stress anomaly, that then resulted in stronger ENSO variability.…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhang (1993), the intensity of convection activity is weaker when the SST is lower. The climatological weak convective activity leads to weak atmospheric responses to SST forcing (Kim et al 2011;Jang et al 2013;Ham and Kug 2012;Kug et al 2012;Watanabe et al 2012). The weaker convective response to lower SST caused by chlorophyll reduces the Bjerkness feedback, and hence suppresses the role of the atmosphere on ENSO dynamics.…”
Section: Influence Of Marine Biology On the Enso Magnitudementioning
confidence: 99%